2019
DOI: 10.1177/0951484819845840
|View full text |Cite
|
Sign up to set email alerts
|

The future state of patient engagement? Personal health information use, attitudes towards health, and health behavior

Abstract: The past decade has given rise to interest in the effects of health care information on personal well-being. However, investigations to-date typically centered on mass communication programs in health rather than on individuals’ psychosocial characteristics, agency, and behaviors associated with their engagement with this information. Considering this gap, we examined whether the availability of personal health information is associated with health prevention behaviors in the United States. Using multivariable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…According to the IMB model, information or motivation alone may not be sufficient to drive behaviour change; behavioural skills are needed as intervening determinants of behaviour change. Previous research has demonstrated that knowledgeable and motivated individuals who possess the relevant behavioural skills are more likely to put into practice the recommended guidelines and behaviours (Anderson et al, 2006;Hearld et al, 2019). In this study, in line with the IMB model, self-efficacy as a behavioural skill has been predicted to mediate the relationships between antecedent factors (online social capital and internet use for health information) and dietary supplement usage.…”
Section: Mediation Effect Of Self-efficacysupporting
confidence: 67%
See 1 more Smart Citation
“…According to the IMB model, information or motivation alone may not be sufficient to drive behaviour change; behavioural skills are needed as intervening determinants of behaviour change. Previous research has demonstrated that knowledgeable and motivated individuals who possess the relevant behavioural skills are more likely to put into practice the recommended guidelines and behaviours (Anderson et al, 2006;Hearld et al, 2019). In this study, in line with the IMB model, self-efficacy as a behavioural skill has been predicted to mediate the relationships between antecedent factors (online social capital and internet use for health information) and dietary supplement usage.…”
Section: Mediation Effect Of Self-efficacysupporting
confidence: 67%
“…age, education level) and situational factors (e.g. social support, socio-economic status) (Hearld et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Such criticism can be considered to be valid for a small subset of available m-health apps. Yet, based on the evidence from a wide range of studies (Hearld et al , 2019; Shapiro and Kamal, 2021; Tavares and Oliveira, 2016), it can be argued that mobile apps’ benefits for public health outweigh such concerns and m-health apps can provide tangible value in improving individual health and subsequently decrease the burden on health systems.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Self-care can also increase their life satisfaction [ 8 ], well-being [ 9 ], quality of life [ 10 ], and, most importantly, ability to age in place [ 11 ]. However, self-care is easier said than done, especially for aged individuals who face barriers such as lack of medication and disease management knowledge, motivation and confidence in taking care of themselves, physical strength, and social support [ 12 , 13 ]. In addition, social determinants of health, such as low educational level, separation from a spouse, and advancing age may impair one’s ability to self-care since these factors affect a person’s capacity, opportunity, and engagement to make the healthy behavioral change [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%